Odpowiedź:
1 i 3/4 *1 i 1/7 - 3 : 4 i 1/2= 7/4 *8/7 -3 : 9/2 ( skracamy 8 i 4 przez 4, oraz 7 i 7
przez 7)= 2 - 3*2/9 ( skracamy 3 i 9 przez 3)=2 - 2/3 = 1 i 3/3-2/3 =1 i 1/3
1 i 5/7 *( 2 i 3/4 - 1 i 2/3 : 4(= 1 i 5/7 *( 2 i 3/4 - 5/3*1/4)= 1 i 5/7 *(2 i 3/4-5/12)=
= 1 i 5/7 *( 2 i 9/12 - 5/12)= 12/7 *2 i 4/12 =12/7*28/12 ( skr. 12 i 12 przez 12
oraz 28 i 7 przez 7)= 4
3 i 1/3 *( 2 i 1/4 - 1 i 1/2 :5) = 3 i 1/3 *( 2 i 1/4 - 3/2*1/5)= 3 i 1/3 *( 2 i 1/4- 3/10)=
= 3 i 1/3 *( 2 i 5/20 - 6/20)= 3 i 1/3 *( 1 i 25/20- 6/20)= 3 i 1/3 *1 i 19/20=
= 10/3 *39/20 ( skr.. 3 i 39 przez 3,oraz 10 i 20 przez 10)= 13/2= 6 i 1/2
3 i 1/4 + 1/2 /3 i 1/3 *( 1 i 5/6 - 1 i 1/12)= 3 i 1/4 +2/4 /3 i 1/3 *( 1 i 10/12 -1 i 1/12)=
= 3 i 3/4 / 3 i 1/3 *9/12= 3 i 3/4 /10/3 *9/12 ( skr.. 3 i 9 przez 3, oraz 12 i 10
przez 2)= 3 i 3/4 : 15/6= 15/4 *6/15 ( skr.. 15 i 15 przez 15, oraz 4 i 6 przez
2)=1/2*3=3/2= 1 i 1/2
Szczegółowe wyjaśnienie: